PEMANTAUAN KEANEKARAGAMAN ZINGIBERACEAE DI DAS JENGOK, BANJARAN, KRANJI, DAN PELUS WILAYAH PURWOKERTO - Pudji Widodo; Yayu Widiawati; Sukarsa Sukarsa (Agroland: Jurnal Ilmu-ilmu Pertanian, 2006)
An investigation on diversity monitoring of ginger family (Zingiberaceae) was carried out on Jengok, Banjaran, Kranji, and Pelus riverbanks in Purwokerto. This study required conventional surveys and repeated measurements to identify and to evaluate changes. Twelve permanent plots were established in 1990 covering the north, central, and south parts of the rivers. The ginger vegetation in 2005 was compared with data taken in 1990, 1997, and 2003. The result of this study showed that the number of spesies in most of the bank reached the peak in 2003 then decreased again in 2005.